Somalia : Enhanced Heavily-Indebted Poor Countries (HIPC) Initiative-Preliminary Document. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2020)
This Enhanced Heavily Indebted Poor Countries (HIPC) Initiative Program's preliminary document discusses that as per the agreement by the IMF, Somalia can be eligible for debt relief under the Enhanced HIPC Initiative. It provides a clear recognition of Somalia's sustained commitment to key economic and financial reforms under consecutive staff-monitored programs with the IMF. Helping Somalia achieve debt relief and unlock access to the needed resources to increase growth and reduce poverty is a key priority for the IMF. Once Somalia has reached the Completion Point, it would qualify for unconditional debt relief under the HIPC Initiative, and for debt relief under the Multilateral Debt Relief Initiative (MDRI) from the World Bank's International Development Association and the African Development Fund, together with beyond-HIPC assistance from the IMF. Paris Club creditors are also expected to provide further beyond-HIPC assistance at the Completion Point. With HIPC, MDRI and beyond HIPC assistance, Somalia's NPV of debt-to-exports ratio is projected to decline from 491.7 percent in 2018 to 57.0 percent in 2027 and 41.5 percent in 2038.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet